Analysis of the MIR396 gene family and the role of MIR396b in regulating fiber length in cotton. Issue 6 (9th November 2022) - Zhang, Bingbing; Liu, Guoyuan; Song, Jikun; Jia, Bing; Yang, Shuxian; Ma, Jianjiang; Liu, Ji; Shahzad, Kashif; Wang, Wenkui; Pei, Wenfeng; Wu, Man; Zhang, Jinfa; et al.
Abstract: Cotton fiber is one of the most important natural raw materials in the world textile industry. Improving fiber yield and quality has always been the main goal. MicroRNAs, as typical small noncoding RNAs, could affect fiber length during different stages of fiber development. Based on differentially expressed microRNA in the two interspecific backcross inbred lines (BILs) with a significant difference in fiber length, we identified the miR396 gene family in the two tetraploid cotton genomes and found MIR396b_D13 as the functional precursor to produce mature miR396 during the fiber elongation stage. Among 46 target genes regulated by miR396b, the GROWTH‐REGULATING FACTOR 5 gene ( GRF5, Gh_A10G0492 ) had a differential expression level in the two BILs during fiber elongation stage. The expression patterns indicated that the miR396b ‐ GRF5 regulatory module has a critical role in fiber development. Furthermore, virus‐induced gene silencing (VIGS) of miR396b significantly produced longer fiber than the wild type, and the expression level of GRF5 showed the reverse trends of the miR396b expression level. The analysis of co‐expression network for the GRF5 gene suggested that a cytochrome P450 gene functions as an allene oxide synthase ( Gh_D06G0089, AOS ), which plays a critical role in jasmonate biosynthetic pathway. In conclusion, our results revealed that the miR396b‐GRF5 module has a critical role in fiber development. These findings provide a molecular foundation for fiber quality improvement in the future.